Finite time control of remotely operated vehicle / Pooyan Alinaghi Hosseinabadi - Pooyan Alinaghi, Hosseinabadi (2018)
The presence of the uncertainties and external disturbances is one of the unavoidable problems in the control system which is addressed in all objectives of this research. In controller design goal of this research, two different sliding surfaces are proposed to deal with trajectory tracking problem by using two control methods, Nonsingular Terminal Sliding Mode Control (NTSMC) and Adaptive Nonsingular Terminal Sliding Mode Control (ANTSMC) for the nonlinear ROV system with one DOF for pitch angle in presence of various uncertainties and external disturbances. Indeed, both adaptive and non-adaptive controllers based on Nonsingular Terminal Sliding Mode Control (NTSMC) are proposed to provide two alternatives which can adjust by changing operating conditions and dynamics. The key features of all four proposed control designs are finite time stability and robustness against uncertainties and external disturbances which provide by using the sliding mode control concept. The finite time stability proofs for all four-controller design are performed by defining a proper candidate Lyapunov function and based on sliding mode control method for the nonlinear ROV system with one DOF for pitch angle. Numerical simulation results are carried out to make a comparison between them and reveal the correctness of fulfilling trajectory tracking goal in all four controller designs. Also, three well-known performance criteria, ISV, IAE, and ITAE are defined to compare these four designed controllers from various aspects. Furthermore, in another objective of this research a class of full order global finite time observers are designed and proposed for a group of nonlinear systems with uncertainties and external disturbances. The studied nonlinear system is a chain form of nonlinear double integrator subsystems that can describe the dynamic behavior of many real systems, including Remotely Operated Vehicle (ROV), gyroscopes, robot manipulators, ships, submarines, and others. In this research, by using modern mathematical analysis and proofs, the estimation errors between the corresponding states variables of the observer and the nonlinear system converge to a real zero after an adjustable finite time. Also, a mathematical relation is presented for calculating and setting the mentioned finite time. Then, a numerical simulation is carried out on the sample of double integrator nonlinear system of ROV system with one DOF for the pitch angle to determine that the state variables of the proposed observer can accurately estimate the corresponding variables in the nonlinear system. A comprehensive comparison is also made between proposed finite time nonlinear observer and some well-known and recent studies on nonlinear observer design.